Effects of a strength endurance training program on endurance levels - G. Cuadrado; A. M. De Benito; S. Sedano; J. M. Izquierdo; J. C. Redondo; J. C. Granado (Asociación Española de Ciencias del Deporte, 2010)
The purpose of the current study was to determine whether a strength endurance training program of lower limbs isolate can increase endurance levels, both aerobic capacity and aerobic power, in order to adapt the strength training for endurance races. 20 phisically active men participated in the study. They were divided into two groups: control group (GC) (n=10) and experimental group (GE) (n=10). GE carried out a strength endurance training program for ten weeks. Results obtained showed that this type of training regime was useful to improve the performance in an aerobic endurance test. This could be due to an improvement in aerobic capacity, maximal dynamic strength, explosive strength and reactive strength. Moreover, there was a decrease in fat mass without increase in muscle mass. Key Words:  Training, strength endurance, aerobic capacity, anthropometry.